Chemical Solution Deposition of Ferroelectric Hafnium Oxide for Future Lead Free Ferroelectric Devices. (1st January 2015) - Starschich, Sergej; Griesche, David; Schneller, Theodor; Böttger, Ulrich
Abstract : The phase formation and the influence of the type of dopant of an improved routine for chemical solution deposition (CSD) of ferroelectric hafnium oxide films are investigated. Ferroelectric properties for yttrium doping and doping with different elements from the lanthanide group are shown. The samples are prepared using platinum electrodes and a hafnium oxide layer with a thickness of 45 nm. The combination of DTA-TG analysis, thickness measurements and temperature dependent XRD study provide insight into the film formation process during the different fabrication steps. Polarization and capacitance measurements are performed to prove the ferroelectric nature of the deposited layers. The yttrium concentration is varied in a range from 0 mol% to 11 mol% proving to have a strong influence on the ferroelectric properties in agreement with the observation made on atomic layer deposition (ALD) prepared samples. A high remanent polarization of 20 μC cm −2 is attained with a coercitive field of 1.4 MV cm −1 for an yttrium doping concentration of 5.2 mol%. The possibility of depositing ferroelectric hafnium oxide films by CSD provides the opportunity of application for lead free piezoelectric and pyroelectric sensors and actuators and can lead to a better insight into the formation of the ferroelectric phase.